2014
DOI: 10.5851/kosfa.2014.34.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Edible Pork By-products by Means of Yield and Nutritional Composition

Abstract: Basic information regarding the yield and nutritional composition of edible pork by-products, namely heart, liver, lung, stomach, spleen, uterus, pancreas, and small and large intestines, was studied. Our results revealed that the yields varied widely among the pork by-products examined; in particular, liver had the highest yield (1.35%); whereas, spleen had the lowest yield (0.16%). The approximate composition range (minimum to maximum) of these by-products was found to be: moisture 71.59-82.48%; fat 0.28-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
65
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 36 publications
25
65
3
Order By: Relevance
“…Daily fat intake is essential for humans because fat provides energy, enhances food palatability and absorption of vitamins (Seong et al, 2014). The fat content of pork tissues in our study was generally higher than values reported in the literature, which could be due to differences in the feeding regime, breed, body weight at slaughter, or processing method of the meat samples (De Lange et al, 2003;Okrouhla et al, 2009;Park et al, 2012;Seong et al, 2014;Skobrák & Bodnár, 2012;Valaitiene et al, 2017;Williams, 2007). The full-fat BSFLM used in our study might have contributed to the crude fat content of the pork tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily fat intake is essential for humans because fat provides energy, enhances food palatability and absorption of vitamins (Seong et al, 2014). The fat content of pork tissues in our study was generally higher than values reported in the literature, which could be due to differences in the feeding regime, breed, body weight at slaughter, or processing method of the meat samples (De Lange et al, 2003;Okrouhla et al, 2009;Park et al, 2012;Seong et al, 2014;Skobrák & Bodnár, 2012;Valaitiene et al, 2017;Williams, 2007). The full-fat BSFLM used in our study might have contributed to the crude fat content of the pork tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These by-products make up an important portion of the animal's live weight and can provide essential nutrients to consumers who are limited in meat and meat products (Alao et al, 2017;Fayemi et al, 2018;Irshad & Sharma, 2015). However, their consumption is limited and varies among cultures and economic status (Seong et al, 2014). The commercial value of these by-products is also low and limited information on their nutritional quality may be responsible for their low consumption rates (Seong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of PUFA in the liver has been reported to be ten times higher than that of muscles from the same animals [28]. Seong et al [29] also found that the fat content of pork liver was comparable to those of the muscle tissues of cattle. Fats serve as building blocks of membranes and play a key regulatory role in numerous biological functions.…”
Section: Consumption and Nutritional Composition Of Edible By-productsmentioning
confidence: 95%
“…For all crops, livestock/poultry, fisheries/aquaculture categories used for this study, proximate compositions were acquired from international food composition tables or other published compendia and primary sources .…”
Section: Methodsmentioning
confidence: 99%